Relationship between smartphone usage duration and the risk of eye strain complaints - Tjokorda Gde Budi Widiana Putra; Ni Luh Nopi Andayani; Indira Vidiari Juhanna; Made Hendra Satria Nugraha (Universitas Udayana dan Diaspora Taipei Medical University, 2023)
Background: A smartphone is a device that is widely used by various groups, one of which is college students. The use of smartphones by college students can be seen from their needs in the learning process. Smartphones are one of the most significant sources of electromagnetic waves that, if used excessively, might affect eye health. Eye strain is a complaint to the eyes that generally occur due to excessive smartphone use. Objective: This study aimed to examine the relationship between the duration of smartphone use and undergraduate students’ eye strain risk. Methods: This study was a cross-sectional analytical observational study between September 2022 and December 2022. The 104 students in the Physiotherapy Study Program at Faculty of Medicine, Universitas Udayana, who ranged in age from 20 to 23, were the study's participants. Total sampling was used as a non-probability sampling technique. Results: The results of the study found that 16 people (15.4%) had an excellent smartphone usage duration of ≤ 4 hours and 88 people (84.6%) had a lousy smartphone usage duration of > 4 hours. The results of the Spearman Rho non-parametric analysis test showed a relationship between the time of smartphone use and eye strain complaints in students (p= 0.001) with a positive coefficient (r= 0.328). Conclusion: There was a significant relationship between the duration of smartphone use and undergraduate students’ eye strain risk.